Behavior of Antibiotics in the Environment - Boonsaner, Maliwan (Applied Environmental Research, 2013)
Antibiotics have been used to treat human disease and to be given to livestock for disease prevention and growth promotion. Because of their large amount and widely uses, the antibiotics were found in various phases of the environment such as manure, sewage, sludge, surface water, soil, livestock and aquatic animal. The antibiotic could enter the environment and degrade in some extents depending on its physicochemical properties and the environmental conditions. Although. its existing in small amount could not cause any lethal effect but previous studies have shown the resistance effect might occur and disturb the microbial ecosystem.